Efeito antirreabsortivo da atorvastatina na perda óssea alveolar de ratos diabéticos com doença periodontal experimental - Angelino, Gisele Barreto (2020)
Periodontitis (PE) is considered an important cause of tooth loss in adults and has been associated with several systemic diseases, especially diabetes mellitus (DM), which exacerbates the body's immune-inflammatory response. Statins have been reported as drugs with bone anabolic and anti-inflammatory effects. In this context, the aim of this study was to investigate the anti-inflammatory and antiresorptive effects of atorvastatin (ATV) on alveolar bone loss in diabetic rats. For that, wistar rats (200-220 g) were used, divided into four experimental groups (n = 6): Naïve (N), PE, DM + PE and ATV. Initially, DM + PE and ATV animals were submitted to diabetes by means of intraperitoneal (ip) administration of streptozotocin (60 mg / kg), in single doses, after 10 hours of fasting. Five days after the induction of DM, the glycemic rate of the rats was measured, in which animals with a rate ≥ 200 mg / dl were considered diabetic. Then, the animals were submitted to periodontitis induced by ligation. The animals in the PE group received saline solution (2 ml / kg-v.o), while the animals in the ATV group received 27 mg / kg, v.o. of ATV, thirty minutes before periodontitis induction until the 11th day. The Naive group was not subjected to any intervention. After 11 days of PE induction, all animals were euthanized. The parameters analyzed were: macroscopic and microtomographic analysis of the bone, microscopic analysis of the periodontium and histometric analysis with osteoblast and osteoclast count / bone perimeter using histochemistry for TRAP. The study's findings showed that DM + PE increased bone loss by 53% compared to the PE group (PE = 2.00 ± 0.405; DM + PE = 4.33 ± 0.764) with low values of trabecular thickness and bone volume (Tb.Th and BV / TV). In addition, they had a higher intensity of the inflammatory infiltrate (DM + PE = score 3) and an increase in the number of osteoclasts (42%) and a relative reduction in the number of osteoblasts (22%), showing that diabetes potentiated bone loss. Macroscopic, microtomographic and histomorphometric analyzes showed that animals treated with ATV showed better results in the volumetric and linear parameters of bone tissue, in addition to reducing the inflammatory infiltrate (mean score 2) when compared to the DM + PE group (score 3). ATV increased the number of osteoblasts (DM + PE: 0.42 ± 0.007; ATV: 0.09 ± 0.02) while reducing the number of osteoclasts by 34.1% compared to DM + PE (p <0.05). In summary, the results of this study showed beneficial effects of ATV in reducing parameters of alveolar and inflammatory bone resorption in exacerbated conditions such as diabetes.